Effectiveness of palm oil waste bioconversion using maggot as organic fertilizer on the growth of pakcoy (Brassica rapa L.) - Istiqomah, Hikmah Nur; Battong, Umar; Rahmisari, Hellina (Jurnal Agrotek Ummat, 2025)
The increasing generation of palm oil waste poses a serious challenge as it can cause environmental pollution if left unutilized. One environmentally friendly solution is to convert palm oil waste into organic fertilizer through maggot bioconversion. This study aimed to mitigate environmental impacts by converting palm oil waste into organic fertilizer using Black Soldier Fly (BSF) larvae and to evaluate its effects on the growth of pakcoy (Brassica rapa L.). The experiment was conducted in Tepian Batang Village, Paser Regency, East Kalimantan, using a two-factor randomized block design with three kasgot (maggot compost) doses (40 g, 80 g, 120 g) and three types of palm oil waste-based growing media (empty fruit bunches, decomposed fronds, and palm ash), each applied at 150 g. Growth parameters observed included plant height, number of leaves, fresh weight, and dry weight of pakcoy. The results showed that the combination of 80 g kasgot and 150 g decomposed fronds (K2M2) increased plant height to 3.67 cm (↑11% compared to the overall mean), leaf number to 10.40 (↑15%), and fresh and dry weight to 47.75 g (↑28%). This combination proved most effective in accelerating vegetative growth of pakcoy. These findings highlight the potential of utilizing palm oil waste as a high-quality organic fertilizer to support sustainable agriculture and circular economy initiatives.